2006
DOI: 10.1128/iai.00012-06
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Human Fallopian Tube Epithelial Cells withNeisseria gonorrhoeaeProtects Cells from Tumor Necrosis Factor Alpha-Induced Apoptosis

Abstract: Following infection withThe female reproductive tract is an immunologically unique site which must respond to a diverse array of sexually transmitted pathogens and must also be tolerant to allogeneic sperm and to conceptuses. Pelvic inflammatory disease (PID) is an acute clinical syndrome associated with the ascending spread of microorganisms through the female reproductive tract (80). PID encompasses a multitude of inflammatory conditions of the upper reproductive tract organs, with the majority of proven cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 86 publications
3
49
0
1
Order By: Relevance
“…Alternatively, bacterial pathogens could inhibit apoptosis during infection, which provides a survival benefit for the bacteria to survive and replicate inside host cells (10,21,32,38,43,55). In the present study, we have demonstrated that Salmonella-induced apoptosis at the sites of infection in mice lacking Akt2 and Akt2 deficiency renders these mice more susceptible to infection, suggesting that apoptosis may play an important role in the pathogenesis of Salmonella-induced colitis.…”
Section: Discussionmentioning
confidence: 52%
“…Alternatively, bacterial pathogens could inhibit apoptosis during infection, which provides a survival benefit for the bacteria to survive and replicate inside host cells (10,21,32,38,43,55). In the present study, we have demonstrated that Salmonella-induced apoptosis at the sites of infection in mice lacking Akt2 and Akt2 deficiency renders these mice more susceptible to infection, suggesting that apoptosis may play an important role in the pathogenesis of Salmonella-induced colitis.…”
Section: Discussionmentioning
confidence: 52%
“…TNF-a has been associated with the cell and tissue damage observed in gonococcal salpingitis (McGee et al 1992, Morales et al 2006). This damage is correlated with increased TNF-a release by epithelium cells of the human oviduct induced by gonococcal infection (McGee et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…These effects may involve a direct interaction between the cells of the female reproductive tract and the different components of the seminal plasma and/or spermatozoa to modulate the immune system resulting in cellular and molecular changes along the female reproductive tract (reviewed in Sharkey et al (2007)). Tumour necrosis factor-a (TNF-a) is a cytokine associated with immune responses in the female genital tract (Tremellen et al 1998, Maisey et al 2003, Morales et al 2006. Furthermore, transcripts of TNF-a and their receptors are expressed in mice, bovine and human oviduct (Hunt et al 1993, Srivastava et al 1996, Wijayagunawardane et al 2003, Reyes et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ngo infection induces damage to ciliated cells primarily, leading to a loss in ciliary activity and eventually to sloughing of cells from the epithelium Stephens et al, 1987]. Cell death in the FT epithelium has been shown to correlate with the up-regulated production of tumour necrosis factor (TNF)-α by the FT epithelium [McGee et al, 1992;McGee et al, 1996;Morales et al, 2006] and it is likely that gonococcal los lipooligosaccharides (LOS) and peptidoglycan fragments are key stimulators of this TNF-α release Melly et al, 1981;Melly et al, 1984]. In previous studies, we observed an apoptotic phenotype in cells of FT explant epithelium following Ngo infection and demonstrated that TNF-α mediated cell death by apoptosis in primary FT epithelial cells occurs in vitro [Morales et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Cell death in the FT epithelium has been shown to correlate with the up-regulated production of tumour necrosis factor (TNF)-α by the FT epithelium [McGee et al, 1992;McGee et al, 1996;Morales et al, 2006] and it is likely that gonococcal los lipooligosaccharides (LOS) and peptidoglycan fragments are key stimulators of this TNF-α release Melly et al, 1981;Melly et al, 1984]. In previous studies, we observed an apoptotic phenotype in cells of FT explant epithelium following Ngo infection and demonstrated that TNF-α mediated cell death by apoptosis in primary FT epithelial cells occurs in vitro [Morales et al, 2006]. Eventually, resolution of the inflammatory response and cell death involves a process of repair by infiltrating fibroblasts that leads to permanent scarring, eventual functional impairment of the tubes and irreversible infertility [Westrom and Wolnerhanssen, 1993].…”
Section: Introductionmentioning
confidence: 99%